চক চত্বর: redevelopment of Chawk Bazar market complex as an impressionistic memory lane, Chawk Bazar, Old Dhaka - Rahman, Athena (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2023.